因式分解(x平方-2x)平方-3x平方+6x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 09:20:38
因式分解(x平方-2x)平方-3x平方+6x因式分解(x平方-2x)平方-3x平方+6x因式分解(x平方-2x)平方-3x平方+6x(x平方-2x)平方-3x平方+6x=(x²-2x)
因式分解(x平方-2x)平方-3x平方+6x
因式分解(x平方-2x)平方-3x平方+6x
因式分解(x平方-2x)平方-3x平方+6x
(x平方-2x)平方-3x平方+6x
=(x²-2x)²-3(x²-2x)
=(x²-2x)(x²-2x-3)
=x(x-2)(x-3)(x+1)
原式=(x²-2x)²-3(x²-2x)
=(x²-2x)(x²-2x-3)
=x(x-2)(x-3)(x+1)
(x*2-2x)*2-3x*2+6x=(x*2-2x-3)(x*2-2x)=x(x+1)(x-2)(x-3)
因式分解:2x平方+3x+1
x的平方-3x+2 因式分解
x的平方-3x+2 因式分解
x平方+2x+3因式分解
3x的平方+x-2因式分解.
因式分解:X平方-xy-2y平方+3x+2
-3x平方-6x平方-3xy平方 因式分解?
因式分解:(x平方+x)(x平方+x-3)-18
(x平方+4x+8)平方+3x(x平方+4x+8)+2x平方因式分解
因式分解,(x的平方+3x)的平方-2(x的平方+3x)-8
因式分解 (x的平方+3x)的平方-2(x的平方+3x)-8
因式分解2(x平方 x)平方-3(x平方 x)-2
(x平方+2x)平方-3(x平方+2x)-4 因式分解
(x平方-3x)的平方-2x的平方+6x+8因式分解
(2x平方-3x+1)平方-18x平方+27x-19,求因式分解,
因式分解(x平方-2x)平方-3x平方+6x
因式分解;3x平方y平方+3x平方-2y平方-2
因式分解;3x平方y平方+3x平方-2y平方-2